2000
DOI: 10.1152/jappl.2000.89.1.176
|View full text |Cite
|
Sign up to set email alerts
|

Exercise induces lipoprotein lipase and GLUT-4 protein in muscle independent of adrenergic-receptor signaling

Abstract: Exercise increases the expression of lipoprotein lipase (LPL) and GLUT-4 in skeletal muscle. Intense exercise increases catecholamines, and catecholamines without exercise can affect the expression of both LPL and GLUT-4. To test the hypothesis that adrenergic-receptor signaling is central to the induction of LPL and GLUT-4 by exercise, six untrained individuals [age 28 +/- 4 (SD) yr, peak oxygen uptake 3.6 +/- 0.3 l/min] performed two exercise bouts within 12 days. Exercise consisted of cycling at approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 36 publications
2
66
2
Order By: Relevance
“…We purposely waited 48 h after the last bout of exercise before conducting our follow-up studies so that we could evaluate the long-term rather than the acute effects of the exercise (26). The TG-lowering effect of exercise is mediated by an increase in lipoprotein lipase in skeletal muscle, and this adaptation appears to require rather vigorous exercise and reverses rapidly (3,22). The BP-lowering effect of exercise is largely a short-term response that is generally lost within 24 h (24).…”
Section: Discussionmentioning
confidence: 99%
“…We purposely waited 48 h after the last bout of exercise before conducting our follow-up studies so that we could evaluate the long-term rather than the acute effects of the exercise (26). The TG-lowering effect of exercise is mediated by an increase in lipoprotein lipase in skeletal muscle, and this adaptation appears to require rather vigorous exercise and reverses rapidly (3,22). The BP-lowering effect of exercise is largely a short-term response that is generally lost within 24 h (24).…”
Section: Discussionmentioning
confidence: 99%
“…While muscular activity has no substantial effect on appetite or caloric intake, 22 physical activity could be important for the regulation of body composition by repartition fuel toward the active site. 23,24 Previous studies have shown that greater physical activity can lead to greater storage of glycogen 2 and triglycerides 25 in the recruited skeletal muscle. Conversely, Simsolo et al 26 demonstrated that the decreased physical activity generates a condition favoring triglyceride partitioning to adipose tissue storage in contrast to skeletal muscle.…”
Section: Detrained Dancers Exhibit Increased Insulin S-y Chen Et Almentioning
confidence: 99%
“…As such, regulation of GLUT4 expression is seen as a potential therapeutic target for the management and treatment of insulin resistance in disorders such as type 2 diabetes. An acute bout of exercise increases GLUT4 transcription (4) and gene (5) and protein expression (6). A binding region on the GLUT4 promoter for the myocyte enhancer factor 2 (MEF-2) transcription factor is required for this response (7).…”
mentioning
confidence: 99%